2019
DOI: 10.1021/acs.langmuir.9b01523
|View full text |Cite
|
Sign up to set email alerts
|

Curcumin Encapsulation in Multilayer Oil-in-Water Emulsion: Synthesis Using Ultrasonication and Studies on Stability and Antioxidant and Release Activities

Abstract: Curcumin is a natural polyphenol compound obtained from the turmeric plant, having numerous promising health benefits. To deliver curcumin into the human body, it is necessary to develop an efficient carrier system for its encapsulation such that the physicochemical properties of curcumin can be preserved during storage. In this study, the encapsulation stability, antioxidant activity, and release properties of curcumin encapsulated in the primary emulsion (PE: 0.0022% (w/w) curcumin, 9.99% (w/w) oil, 0.9% (w/… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

1
21
0
2

Year Published

2020
2020
2022
2022

Publication Types

Select...
7
1

Relationship

0
8

Authors

Journals

citations
Cited by 56 publications
(29 citation statements)
references
References 37 publications
1
21
0
2
Order By: Relevance
“…A recent study showed that the multilayer emulsions formed with ovalbumin as the first layer and gum arabic as the second layer had much smaller droplet sizes and better stability than those formed with the opposite arrangement [64]. Other protein-polysaccharide combinations that have been applied to prepare multilayer emulsions include gelatinchitosan [91], whey protein-alginate [92,93], lactoferrin-alginate [59,94,95], and soy βconglycinin-pectin [96]. Multilayer emulsions can also be stabilized using two or more polysaccharides, one that acts as an emulsifier and the others that form additional layers.…”
Section: Multilayer Emulsionsmentioning
confidence: 99%
“…A recent study showed that the multilayer emulsions formed with ovalbumin as the first layer and gum arabic as the second layer had much smaller droplet sizes and better stability than those formed with the opposite arrangement [64]. Other protein-polysaccharide combinations that have been applied to prepare multilayer emulsions include gelatinchitosan [91], whey protein-alginate [92,93], lactoferrin-alginate [59,94,95], and soy βconglycinin-pectin [96]. Multilayer emulsions can also be stabilized using two or more polysaccharides, one that acts as an emulsifier and the others that form additional layers.…”
Section: Multilayer Emulsionsmentioning
confidence: 99%
“…The free radical scavenging rate of Cur‐Ne was shown in Figure 6(a). The DPPH and ABTS free radical scavenging rates of Cur‐Ne at the concentration of 300 μmol/L were 83.52 ± 3.02% and 99.63 ± 0.48%, respectively, which were higher than that of the curcumin nanoemulsion prepared by Saharan (Carpenter et al., 2019). The high antioxidant activity of Cur‐Ne was due to the joint action of curcumin and oregano essential oil.…”
Section: Resultsmentioning
confidence: 83%
“…The antioxidant activity of curcumin is attributed to its unique conjugated structure, which shows typical radical-trapping ability as a chain-breaking antioxidant [ 55 ]. Numerous studies reported enhanced antioxidant properties of the curcumin encapsulated in colloidal system such as liposomes [ 56 ], polymeric microparticles [ 57 ], hydrogel beads [ 58 ], nanoparticles [ 59 ], and microemulsions [ 60 ]. Curcumin containing microemulsion and microemulsion gel was developed with grape seed oil as a lipid phase, where the synergistic antioxidant activity of the optimized microemulsion and gel microemulsions was observed due to the presence of grape seed oil which helped effectively encapsulate and preserve the antioxidant stability of curcumin [ 61 ].…”
Section: Resultsmentioning
confidence: 99%